La représentation de la censure dans la série romanesque japonaise Library Wars : une lecture à la lueur de Fahrenheit 451 - Maxime Danesin (ReS Futurae, 2017)
Throughout the 20th century, Dystopian Literature was used as a “laboratory of the worst” (Faye, 1993) by authors engaged against Totalitarism and Censorship. However, Censorship is still ever-present; it has adapted to its postmodern context, assuming new forms. Still, the Dystopian Literature’s torch burns vividly in Japan. It has developed a rich production of science fiction, born from a culture mixing between local and foreign elements; it has become inevitable in these times of globalisation. Among contemporary works, Arikawa Hiro’s Library Wars (Toshokan Sensō), drew our attention. This novelistic series of four volumes, published from 2006 to 2007, is staged in a democratic Japan that is being corrupted by a Censorship Law, promulgated for the sake of morality, and where Library Corps try to defend free speech. Multi-genre (dystopian, uchronian, love-comedy), written in a local media form – light novel –, it has been widely successful, earning the author the Seiun Award 2008 – the Japanese equivalent of the Hugo Award. Arikawa’s work surprises with its original approach of the theme of Censorship and the way its story has a strong resonance with Ray Bradbury’s dystopian novel Fahrenheit 451. In this article, we show how Library Wars inherits et continues the theme of Censorship in science-fiction, and thus reconfigures the bradburyian schema according to its own, contemporary and Japanese, context.